Reduced Insulin Receptor Expression Enhances Proximal Tubule Gluconeogenesis. Issue 2 (27th June 2016) - Pandey, Gaurav; Shankar, Kripa; Makhija, Ekta; Gaikwad, Anil; Ecelbarger, Carolyn; Mandhani, Anil; Srivastava, Aneesh; Tiwari, Swasti
ABSTRACT: Reduced insulin receptor protein levels have been reported in the kidney cortex from diabetic humans and animals. We recently reported that, targeted deletion of insulin receptor (IR) from proximal tubules (PT) resulted in hyperglycemia in non‐obese mice. To elucidate the mechanism, we examined human proximal tubule cells (hPTC) and C57BL/6 mice fed with high‐fat diet (HFD, 60% fat for 20 weeks). Immunoblotting revealed a significantly lower protein level of IR in HFD compare to normal chow diet (NCD). Furthermore, a blunted rise in p‐AKT 308 levels in the kidney cortex of HFD mice was observed in response to acute insulin (0.75 IU/kg body weight, i.p) relative to NCD n = 8/group, P < 0.05). Moreover, we found significantly higher transcript levels of phosphoenolpyruvate carboxykinase (PEPCK, a key gluconeogenic enzyme) in the kidney cortex from HFD, relative to mice on NCD. The higher level of PEPCK in HFD was confirmed by immunoblotting. However, no significant differences were observed in cortical glucose‐6‐phosphatase (G6Pase) or fructose‐1, 6, bisphosphosphatase (FBPase) enzyme transcript levels. Furthermore, we demonstrated insulin inhibited glucose production in hPTC treated with cyclic AMP and dexamethasone (cAMP/DEXA) to stimulate gluconeogenesis. Transcript levels of the gluconeogenic enzyme PEPCK were significantly increased in cAMP/DEXA‐stimulated hPTC cells (n = 3, P < 0.05), and insulin attenuated this upregulation Furthermore, the effect of insulin on cAMP/DEXA‐induced gluconeogenesis and PEPCK induction was significantly attenuated in IR (siRNA) silenced hPTC (n = 3, P < 0.05). Overall the above data indicate a direct role for IR expression as a determinant of PT‐gluconeogenesis. Thus reduced insulin signaling of the proximal tubule may contribute to hyperglycemia in the metabolic syndrome via elevated gluconeogenesis. J. Cell. Biochem. 118: 276–285, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Insulin receptor silencing resulted in transcriptional induction of gluconeogenic enzyme along with increased gluconeogenesis in human proximal tubule cells. In addition, reduced insulin receptor expression, blunted insulin signaling, and increased gluconeogenic enzyme levels were found in the kidney cortex of high‐fat fed mice. Overall the findings suggest that, impaired insulin sensitivity of proximal tubule may affect whole body glucose homeostasis and thus further contribute to hyperglycemia in the metabolic syndrome via elevated gluconeogenesis in the kidney.